The Grameen Bank model of microcredit and its relevance for South Africa - Akpan, Iniobong Wilson (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2005)
Among the reasons for financial exclusion is the fact that the poor, being largely illiterate and unemployed, are traditionally perceived as 'bad credit risks'. This is the dominant perception of the poor in the formal credit markets "“ a perception that also exists in the microcredit sector. In other words, while information asymmetry is a recognized problem in lender-borrower relationships, lenders consider the problem particularly severe when they contemplate doing business with the poor. A contrasting paradigm, such as the one adopted by Grameen Bank of Bangladesh, views the poor as possessing economic potentials that have not been tapped "“ that is, as 'good credit risks'. Grameen Bank's microcredit features appear to have successfully mitigated the problems of information asymmetry and, to a large extent, made it possible for the poor to access microenterprise credit. Using the Grameen Bank model as a benchmark, this study examined the lending features of private sector microlenders in South Africa and those of KhulaStart (credit) scheme. The aim was to identify how the lending features affect microenterprise credit access. Primary data were obtained through interviews, while relevant secondary data were also used in the study. A key finding of the study was that while the Khulastart scheme was, like Grameencredit, targeted at the poor, the method of its delivery appeared diluted or unduly influenced by the conventional (private sector) paradigm that pre-classifies people as 'good' or 'bad' credit risks. As a result, the scheme was not robust enough to support microenterprise credit access. This has consequences for job-creation and poverty reduction. Based on the findings, the study maintains that a realistic broadening of microenterprise credit access will not occur unless there is a fundamental paradigm shift in microcredit practices, and unless measures designed to mitigate information asymmetries are sensitive to the historical, economic and sociocultural realities of the South African poor.
Keywords: Grameen Bank; Microfinance -- South Africa; Microfinance -- Bangladesh; Credit -- Management; Risk management; Poor -- Finance, Personal; South Africa -- Economic conditions; Bangladesh -- Economic conditions